Consensus-based distributed control for economic dispatch problem with comprehensive constraints in a smart grid - Cao, J.; Yu, M.; Tung, J. (EAI Endorsed Transactions on Energy Web, 2014)
Economic dispatch problem (EDP) has become more complex and challenging in power systems due to the introduction of smart grids. In a smart grid, it’s expensive and unreliable for the existing centralized controller to achieve a minimum cost when generating a certain amount of power. In this work, we define a quadratic cost function and comprehensive constraints to improve the consensus algorithm. We propose a distributed control approach based on the improved consensus algorithm to solve the EDP in a smart grid. Different from the centralized approach, the proposed approach enables each generator to collect the mismatch between power demands and generations in a distributed manner. The mismatch in power is used as a feedback for each generator to adjust its power generation. The incremental cost of the generator is selected as the consensus quantity that converges to a common value eventually. Simulation results of different case studies are provided to demonstrate the effectiveness of the proposed algorithm. The comparisons between the proposed approach and the existing ones are also presented.
Keywords: consensus algorithm; convergence; distributed control; economic dispatch problem; incremental cost; smart grid